A new three‐dimensional glass scaffold increases the in vitro maturation efficiency of buffalo (Bubalus bubalis) oocyte via remodelling the extracellular matrix and cell connection of cumulus cells. Issue 2 (3rd January 2020) - Shen, Penglei; Xu, Jie; Wang, Ping; Zhao, Xin; Huang, Ben; Wu, Fei; Wang, Lulu; Chen, Weili; Feng, Yun; Guo, Zhenwei; Liu, Xiaohua; Deng, Yanfei; et al.
Abstract: At present, many three‐dimensional (3D) culture systems have been reported, improving the oocyte quality of in vitro maturation (IVM), yet the mechanism still needs to be further explored. Here we examined the effects of a new self‐made 3D glass scaffold on buffalo oocyte maturation; meanwhile, the underlying mechanism on buffalo oocyte maturation was also detected. Compared to the two‐dimensional (2D) glass dish culture, results revealed that the 3D culture can improve the first polar body rate of oocytes, subsequent cleavage and blastocysts rate of parthenogenetic activation embryos ( p < .05). The extracellular matrix‐related proteins COL1A1, COL2A1, COL3A1, FN and cell connection‐related proteins N‐cadherin, E‐cadherin, GJA1 were found higher in cumulus cells of 3D culture. Moreover, in cumulus cells, proteins of the PI3K/AKT pathway reported being regulated by FN and E‐cadherin including PI3K P85 and p‐AKT were also higher in 3D culture. Furthermore, proapoptosis proteins P53, BAX, caspase‐3 were lower in both cumulus cells and oocytes in 3D culture, while proteins PCNA and BCL2 showed the opposite result. Results also showed that the apoptosis was inhibited, and the proliferation was enhanced in cumulus cells of 3D culture. Finally, the cumulus expansion‐related genes HAS2, CD44, HMMR, PTX3, PTGS2 were found higher in cumulus cells of 3D culture. Taken together, the 3D culture could promote oocyte maturation by regulating proteins correlated with the ECM, cell connection and PI3K/AKT pathway, inhibiting the apoptosis of cumulus cells and oocytes, enhancing the proliferation of cumulus cells and the cumulus expansion.